Doing more among institutional boundaries: Platform‐enabled government in China. - Zeng, Yu; Zhang, Quan; Zhao, Qi; Huang, Huang (Review of Policy Research, 2023)
The concept of Government as a Platform (GaaP) has recently encountered setbacks in practice worldwide. While existing literature on inter‐governmental collaboration has emphasized organizational restructuring and data sharing, this study argues that a pragmatic way to improve administrative efficiency in the absence of formal institutional change is to adopt an alternative model to GaaP: platform‐enabled government. Enabled by innovations of the middle‐tier platform, this new model of platform governance integrates the functions of distributed systems of multiple departments into a sequential workflow without the requirement of institutional reform or sharing proprietary data. To demonstrate how this model facilitates information flow across institutional boundaries and improves collaborative governance, we analyze horizontal, vertical, and public‐private collaboration using a diverse case study design. We examine administrative review, law enforcement, and contact tracing during the pandemic in the context of China. Our findings suggest accommodating institutional boundaries is a practical and effective approach to advance the digital government agenda in decentralized contexts.